A aprendizagem da leitura e escrita da criança surda na perspectiva bilíngue - Souza, Eduarda Monteiro de (My University, 2024)
The education of the deaf has many singularities, among which the issue of sign language stands out. From this perspective, bilingual education for the deaf is a right in our country, in which the Brazilian Sign Language (Libras) and the written form of the Portuguese language are used as languages of instruction throughout the educational process. For the deaf person, writing is not the representation of speech, nor is it the representation of Libras. As a result, the literacy processfor deaf children will occur differently than hearing children. Understanding this process and building educational practices that respect the needs of deaf people is a challenge for both research and schools. The general objective of this research is to analyze how the process of learning to read and write the Portuguese language by deaf people has been discussed and studied from a bilingual perspective. The specific objectives are: a) Systematize knowledge production on the acquisition of reading and writing written language by deaf children. b) Identify the specificities of literacy skills for deaf children who use sign language as L1. c) Build principles to support the literacy process of deaf students. The research development method is bibliographic, whose critical analysis is anchored in the understanding of deafness as a linguistic and cultural minority, in the understanding of the subject as active in the learning process, in the constructivist perspective and in the premises of bilingualism for deaf education, aiming to extract , through the analysis of bibliographic materials, the systematic understanding of the process of acquiring reading and writing by deaf people and the construction of educational principles to support this process. The results of the study indicate that most of them deal with teaching methods, and the final product of how children are reading and writing. As a highlight of the specificities of literacy for deaf people, reading and writing are seen as a visual experience. From the analyzes carried out, eight principles were constructed to support the process of reading and writing acquisition by deaf people, based on the framework adopted in the research. At the end, there is a lot of research that can be carried out in the area, in order to contribute and understand the literacy of deaf children. [resumo fornecido pelo autor]
A educação de surdos possui muitas singularidades, dentre elas destaca-se a questão da língua de sinais. Nesta perspectiva, a educação bilíngue para surdos é um direito em nosso país, em que a Língua Brasileira de Sinais (Libras) e a modalidade escrita da Língua Portuguesa são utilizadas como línguas de instrução em todo o processo educativo. Para a pessoa surda a escrita não é a representação da fala, como também não é a representação da Libras. Em decorrência disso, o processo de alfabetização de crianças surdas sucederá de maneira diferente de crianças ouvintes. Compreender esse processo e construir práticas educativas que respeitem as necessidades das pessoas surdas é um desafio, tanto para as pesquisas como para as escolas. O objetivo geral desta pesquisa é analisar como o processo de aprendizagem da leitura e escrita da língua portuguesa pelos surdos tem sido discutido e estudado a partir da perspectiva bilíngue. Tem-se como objetivos específicos: a) Sistematizar produções de conhecimento sobre aquisição de leitura e escrita da língua escrita por crianças surdas. b) Identificar as especificidades da alfabetização da criança surda que utiliza a língua de sinais como L1. c) Construir princípios para apoiar o processo de alfabetização de estudantes surdos. O método de desenvolvimento da pesquisa é bibliográfico, cuja análise crítica é ancorada na compreensão da surdez como minoria linguística e cultural, na compreensão do sujeito como ativo no processo de aprendizagem, pela perspectiva construtivista e nas premissas do bilinguismo para educação de surdos, visando extrair, através da análise dos materiais bibliográficos, a compreensão sistematizada do processo de aquisição da leitura e escrita pelos surdos e a construção de princípios educacionais para apoiar esse processo. Os resultados do estudo apontam que grande parte deles trata sobre métodos de ensino, e o produto final de como está a leitura e a escrita das crianças. Como destaque das especificidades da alfabetização dos surdos tem-se a leitura e escrita como uma experiência visual. A partir das análises realizadas foram construídos oito princípios para apoiar o processo de aquisição da leitura e escrita pelos surdos, tomando por base o referencial adotado na pesquisa. Aponta-se ao final, muitas pesquisas que podem ser realizadas na área, a fim de contribuir e compreender sobre alfabetização de crianças surdas. [resumo fornecido pelo autor]
Keywords: Surdos - Educação; Educação bilíngüe; Aprendizagem; Prática de ensino; Deaf - Education; Education, Bilingual; Learning; Student teaching